siRNA targeting of the human papillomavirus 18 E6 oncogene in hela cells - Reyes, Joyce D.
Extensive studies have demonstrated that the initiation and progression of cervical cancer is associated with high-risk human papilloma virus (HPV) oncogenes that interfere with the activities of cellular tumor suppressors. The development of an anticancer therapy, such as RNA interference, that targets high risk HPV oncogenes can be a specific and effective treatment for cervical cancer. The aim of the present study was to design small interfering RNAs (siRNAs) which target the HPV 18 E6 gene, and primers that will amplify the said gene. siRNAs that target HPV18 E6 were tested in HPV18-positive HeLa cell lines to determine if they can limit the gene transcript in vitro. Two specific siRNAs of HPV18 E6 exon1 and their corresponding scrambled siRNAs were synthesized and introduced into HeLa cells by liposome transfection. HPV18 E6 gene transcripts were measured after transfection by qRT-PCR. The efficiency of siRNA was evaluated by HPV18 E6 relative gene expression using the Ct method of calculation. As normalized with B2M and GAPDH, silencing rates of s1 were 56% and 60%; while s2 suppressed the original mRNA by 75% and 73%, respectively. The scrambled siRNAs, c1 and c2, did not significantly affect the mRNA expression level in the transfected cells. In both s1 and s2, the greatest silencing effect was observed at 24 hours post transfection, and this was sustained through 48 hours. The mean reductions in gene expressions were significantly different between the HeLaS and HeLaC groups (p<0.001), and the reductions over time were significant as well (p<0.001). The mean reductions in gene expressions were significant between s1 and s2 regions (p=0.001). There seemed to be no difference in the mean reductions in gene expressions between the reference genes (p=0.971). In conclusion, this study was able to show that the siRNAs that were designed to target HPV18 E6 exon1 can limit gene expression in vitro.
Computer print out.